WORKSHOP PENGGUNAAN GOOGLE FORM SEBAGAI MEDIA EVALUASI PEMBELAJARAN PADA DOSEN-DOSEN FAKULTAS STUDI ISLAM - Hamdan Husein Batubara (Universitas Islam kalimantan MAB, 2016)
The dedication of society service aims to increase insight and skill of lecturer in using Google Form application as media of learning evaluation at Islamic University of Kalimantan MAB Banjarmasin. Partners involved in science and technology for society (IbM) is 15 lecturers of the Faculty of Islamic Studies UNISKA. The methods of this activity is training in the form of tutorials and discussions about the steps to create an online quiz media using the Google Form application. The results of the activity show that the trainees already understand the principles of creating quiz and are able to create online quiz using the Google Form application.